Analysis of experience-regulated transcriptome and imprintome during critical periods of mouse visual system development reveals spatiotemporal dynamics. (15th January 2018) - Hsu, Chi-Lin; Chou, Chih-Hsuan; Huang, Shih-Chuan; Lin, Chia-Yi; Lin, Meng-Ying; Tung, Chun-Che; Lin, Chun-Yen; Lai, Ivan Pochou; Zou, Yan-Fang; Youngson, Neil A; Lin, Shau-Ping; Yang, Chang-Hao; et al.
Abstract: Visual system development is light-experience dependent, which strongly implicates epigenetic mechanisms in light-regulated maturation. Among many epigenetic processes, genomic imprinting is an epigenetic mechanism through which monoallelic gene expression occurs in a parent-of-origin-specific manner. It is unknown if genomic imprinting contributes to visual system development. We profiled the transcriptome and imprintome during critical periods of mouse visual system development under normal- and dark-rearing conditions using B6/CAST F1 hybrid mice. We identified experience-regulated, isoform-specific and brain-region-specific imprinted genes. We also found imprinted microRNAs were predominantly clustered into the Dlk1-Dio3 imprinted locus with light experience affecting some imprinted miRNA expression. Our findings provide the first comprehensive analysis of light-experience regulation of the transcriptome and imprintome during critical periods of visual system development. Our results may contribute to therapeutic strategies for visual impairments and circadian rhythm disorders resulting from a dysfunctional imprintome.